STRATEGI PENERAPAN MODEL KEPEMIMPINAN PENDIDIKAN DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN KEARSIPAN - Ferdi Listiadi Putra; Faizatul Khoeriyah, Fety; Sania, Ismatus; Aisyah, Siti; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Archival management is an important element in supporting administrative effectiveness and decision-making processes within an institution. Archives function not only as sources of information, but also as records that provide value for administrative and organizational purposes. In practice, the effectiveness of archival management is influenced by the strategy of applying leadership models in directing, coordinating, and supervising records management systematically. This article aims to examine the strategy of implementing leadership models to improve the effectiveness of archival management. The results show that each leadership model has characteristics that influence the effectiveness and efficiency of records management. Appropriate leadership models can support archive organization, facilitate information access, improve supervision quality, and maintain the sustainability of archival systems in the long term. In addition, effective leadership also plays a role in responding to the development of information needs and supporting more adaptive archival systems. Therefore, the implementation of leadership models becomes an important factor in improving the effectiveness of archival management in institutions.